In vitro tissue microarrays for quick and efficient spheroid characterisation - Ivanov, Delyan Pavlov; Grabowska, Anna M. (Sage, 2018)
Three-dimensional in vitro microphysiological cultures, such as spheroids and organoids, promise increased patient relevance and therapeutic predictivity compared to reductionist cell monolayers. However, high-throughput characterisation techniques for 3D models are currently limited to simplistic live/dead assays. By sectioning and staining in vitro microtissues researchers can examine their structure, detect DNA, RNA and protein targets and visualise them at the level of single cells. The morphological examination and immunochemistry staining for in vitro cultures has historically been done in a laborious manner involving testing one set of cultures at a time. We have developed a technology to rapidly screen spheroid phenotype and protein expression by arranging 66 spheroids in a gel array for paraffin-embedding, sectioning and immunohistochemsitry. The process is quick, mostly automatable and uses 11 times less reagents compared to conventional techniques. Here we showcase the capabilities of the technique in an array made up of 11 different cell lines stained in conventional H&E staining, as well as immunohistochemistry staining for estrogen (ER), progesterone (PR) human epidermal growth factor receptors (Her-2) and TP53. This new methodology can be used in optimising stem cell-based models of disease and development, for tissue engineering, safety screening and for efficacy screens in cancer research.